The β-catenin C terminus links Wnt and sphingosine-1-phosphate signaling pathways to promote vascular remodeling and atherosclerosis - Oliveira Paula, Gustavo H. (2024)
Canonical Wnt and sphingosine- 1- phosphate (S1P) signaling pathways are highly conserved systems that contribute to normal vertebrate development, with key consequences for immune, nervous, and cardiovascular system function; despite these functional overlaps, little is known about Wnt/β- catenin–S1P cross- talk. In the vascular system, both Wnt/β- catenin and S1P signals affect vessel maturation, stability, and barrier function, but information regarding their potential coordination is scant. We report an instance of functional interaction between the two pathways, including evidence that S1P receptor 1 (S1PR1) is a transcriptional target of β- catenin. By studying vascular smooth muscle cells and arterial injury response, we find a specific requirement for the β-catenin carboxyl terminus, which acts to induce S1PR1, and show that this interaction is essential for vascular remodeling. We also report that pharmacological inhibition of the β- catenin carboxyl terminus reduces S1PR1 expression, neointima formation, and atherosclerosis. These findings provide mechanistic understanding of how Wnt/β-catenin and S1P systems collaborate during vascular remodeling and inform strategies for therapeutic manipulation.